Toxicity and resistance levels of phosphine against Tribolium castaneum (Herbst) and Sitophilus oryzae (L.) populations - Behera, Santosh Kumar; Shaw, SS; Rath, PC; Adak, Totan; G, Basana Gowda; Pandi G, Guru Pirasanna; M, Annamalai; Pati, P; Mandol, L; Patil, Naveenkumar B (ORYZA-An International Journal of Rice, 2023)
The most destructive stored grain pests in India are the rust red flour beetle and the rice weevil. The most common method for controlling these two pests in storage is phosphine fumigation. However, frequent and acute or chronic doses of exposure than the recommended doses lead to the development of genetic and morphological resistance by changing their traits towards phosphine.Our recent study aimed to detect phosphine resistance degreesin T. castaneum and S. oryzae populations from twelve locations in Odisha. According to bioassay analysis, for S. oryzae after 24 hrs exposure period forphosphine gas to all the assessed populations, the LC50 value varied from 0.004 mg/l to 0.038 mg/l and the population of one location i.e., Chhata (Kendrapara) was found to have strong resistance to phosphine with 9.50 fold more resistant in comparison with the laboratory population. The phosphine toxicity levels for T. castaneum ranged from the LC50 values of 0.130 mg/l (Kendupali, Barghar) to 0.011 mg/l (Durgapali, Sambalpur), i.e., they were 13.00 and 1.10 times more resistant than the laboratory-susceptible population. It is possible that increasing resistance levels is due to storage structures are not tightly sealed during fumigation leading to sub-lethal phosphine concentration and lack of knowledge about fumigation procedures.